Guided surgery in esthetic region - Motta, Marcos; Monsanoy, Rodrigo; Velloso, Glauco Rodrigues; De Oliveira Silva, Julio Cesar [UNESP]; Luvizuto, Eloa Rodrigues [UNESP]; Margonar, Rogerio; Queiroz, Thallita Pereira (Wolters Kluwer, 2016)
The placement of dental implants and subsequent placement of immediate temporary dentures after extractions has become a treatment modality accepted by the scientific community. In addition to the functional factor, the surgical procedure in a single stage in the anterior region of the maxilla offers an esthetic appearance, and relieves the psychological concerns of patients. To guarantee the success and longevity of treatments performed, the fabrication of surgical guides is a helpful method in these situations. Guided surgery has gained attention because it restores esthetics with immediate restoration, provides the patient with comfort in addition to dispensing with the need for performing surgical flaps. This auxiliary method allows the position and design of the implant, as well as the perforation sequence to be programmed, thus optimizing the clinical results. In this study, the authors present a clinical case of a patient who was submitted to extraction and subsequent implant placement with immediate loading in the anterior region of the maxilla, performed in a satisfactory manner.
Keywords: CAD/CAM; Dental implants; Guided surgery; Prosthesis